2019
DOI: 10.1186/s10152-019-0522-1
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of fish Poecilia velifera and their potential as bioindicators of wetland restoration progress

Abstract: Fish harbor a high diversity of parasites that play an important role for the ecosystem. Because these parasites have different life-cycle traits, changes in their populations or communities may provide useful information related to ecosystem health. Highly stressful conditions may reduce parasite communities or populations. However, it is not a rule since host-parasite interactions are hardly predictable. In this study, macroparasites of the fish sailfin molly (Poecilia velifera) from three sites (conserved, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Consequently, swamp habitats have a higher diversity of ectoparasites compared to other habitats. Several studies inform that monogenean parasites are more commonly found in wetland areas (including swamps) with still water and low pollution levels (Krause et al 2010;Morales-Serna et al, 2019). Ansyari et al (2020) also revealed a similar result where Dactylogyrus sp.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, swamp habitats have a higher diversity of ectoparasites compared to other habitats. Several studies inform that monogenean parasites are more commonly found in wetland areas (including swamps) with still water and low pollution levels (Krause et al 2010;Morales-Serna et al, 2019). Ansyari et al (2020) also revealed a similar result where Dactylogyrus sp.…”
Section: Discussionmentioning
confidence: 90%
“…Parasitisme is echter vooral onderzocht in het kader van de medische wetenschap. Recent is meer aandacht voor parasitisme als stuurfactor voor biodiversiteit en als bio-indicator in de aquatische ecologie (Morales-Serna et al, 2019;Sures et al, 2017). In een studie in beken werden in en aan 20-100% van de geleedpotigen parasieten gevonden (Grabner, 2017).…”
Section: Parasitismeunclassified
“…A various research had documented that the nematode genus Cucullanus Muller, 1777 (Cucullanidae) was the dominating variant, not only in freshwater, but also in brackish and marine waters around the world. Morales-Serna et al (2019) recently documented that Cucullanus sp. had prevalence of 14 % and mean intensity of 1.9 in the intestines of the Yucatan molly (Poecilia velifera) caught in the wetlands of Terminos Lagoon, Mexico.…”
Section: Journal Of Sustainabilitymentioning
confidence: 99%